2013
DOI: 10.1017/s175173111200239x
|View full text |Cite
|
Sign up to set email alerts
|

Accurate mathematical models to describe the lactation curve of Lacaune dairy sheep under intensive management

Abstract: Although the intensive production system of Lacaune dairy sheep is the only profitable method for producers outside of the French Roquefort area, little is known about this type of systems. This study evaluated yield records of 3677 Lacaune sheep under intensive management between 2005 and 2010 in order to describe the lactation curve of this breed and to investigate the suitability of different mathematical functions for modeling this curve. A total of 7873 complete lactations during a 40-week lactation perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…The substantial difference of parameters that define the patterns of lactation curve and milk yield between lactation numbers are probably related to the biology of the mammary gland.. By interpreting the biological parameters from Pollott´s model, it can be established that the maximum TMY reached in third lambing is associated with lower decline in the udder cells (DR). This disagrees with the results from the Awassi (Pollott and Gootwine, 2004) and Lacaune sheep (Elvira et al, 2013a), both studies showed that milk yield declined as the ewes aged. Also DR increased and MS declined as lambing number increased.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The substantial difference of parameters that define the patterns of lactation curve and milk yield between lactation numbers are probably related to the biology of the mammary gland.. By interpreting the biological parameters from Pollott´s model, it can be established that the maximum TMY reached in third lambing is associated with lower decline in the udder cells (DR). This disagrees with the results from the Awassi (Pollott and Gootwine, 2004) and Lacaune sheep (Elvira et al, 2013a), both studies showed that milk yield declined as the ewes aged. Also DR increased and MS declined as lambing number increased.…”
Section: Discussioncontrasting
confidence: 99%
“…Flock 1 had the highest TMY, lowest DR (0.12, P = 0.03) and a trend to have the highest level of MSmax (3.43 L, P = 0.08). Hence, higher milk yields are associated with higher MSmax and lower rate of decreasing number of mammary cell due to apoptosis (DR) (Elvira et al, 2013a); fortunately, these parameters were negatively correlated (r = -0.35). MSmax is highly correlated with the peak yield (r = 0.99) (Pollott and Gootwine, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on shape of the lactation curve has mainly addressed milk persistency, trying to find indicator criteria of the slope of the curve after the peak of lactation (Gengler, 1996), or modeling of overall curve shape. Some authors have focused on finding mathematical models that describe the biological processes of milk production by mammary gland cells (Pollott, 2000;Elvira et al, 2013a). Others have proposed a statistical approach by modeling the shape of the curve from elementary controls such as random regression testday models including genetic and nongenetic effects (Menéndez-Buxadera et al, 2010;Mucha et al, 2014;Brito et al, 2017) or by using methods such as principal component analysis (PCA) to sum up the information contained in the data (Carta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Lacaune dairy sheep the lactation peak occurs between the 27 th and 48 th day postpartum depending on the lactation number. Until the 90 th day, 50 % of the total milk yield is usually produced ( Elvira et al, 2013 ). Thus, in this study we covered only the two last thirds of the lactation period where milk yield is already decreasing.…”
Section: Discussionmentioning
confidence: 99%